Examining the Engineering Design Process of First-Year Engineering Students During a Hands-on, In-class Design Challenge - Swenson, Jessica E.; Portsmore, M.; Danahy, E. (Tufts Archival Research Center, 2017)
Engineering design has universally been identified as essential to the practice of engineering. As institutions of higher education seek to improve their undergraduate engineering programs, significant attention has been directed to how to develop and improve students’ engineering design practices. This effort often starts in first-year courses as it is coupled with initiatives to retain students. This paper presents both the adaptation of an existing methodology to study design practices to accommodate an in-class design challenge and initial results from the implementation of that methodology to study groups of students in a first-year LEGO robotics- based engineering course at Tufts University. Preliminary results show students engaged in limited problem scoping and information gathering. These results add to differing results about the practices of first-year engineering, suggesting that context may play a large role in how students invoke design practices. Results also indicate that the majority of time was spent in physical construction and management of group communication. The implications of both of these findings are discussed with respect to instructional design for first-year students along with directions for future research and methodology refinement.